MENINGKATKAN KECERDASAN EMOSIONAL SISWA MELALUI KEBIASAAN MEMBACA AL-QURAN - Jariah, Ainun (Jurnal Studia Insania, 2019)
The purpose of this research is to find out the level and the correlation between the habit of reading the Qur?an to the emotional quotient of student class VIII MTs Al-Hamid Banjarmasin. This research used a quantitative approach. The data collection device uses the Likert scale, scale aspect of the habit of reading Qur?an 38 items, and emotional quotient scale 37 items that have been tested for validity and reliability. The sampling technique used was nonprobability sampling, with a total of 89 peoples ? the data analysis using SPSS software for Windows 21.0. Quantitative data shows the habit of reading Qur?an in the medium category (61,79 percent) and emotional quotient in the medium type (66,29 percent). A correlation analysis results use a Pearson product moment technique in the can calculated r value is 0,460 with p-value 0,000 while the r table is at the 5 percent significance level with N = 89 of 0,213 show off that the habit of reading Qur?an affected the level of emotional quotient. As for the magnitude of the contribution of the practice of reading the Qur?an variable to the emotional quotient of MTs Al-Hamid Banjarmasin in the amount of (rxy2 x 100) or 21,16 percent.